KORELASI ANTARA NEW MEDIA DALAM KOMUNIKASI POLITIK DAN PENDIDIKAN DAKWAH DI ERA DIGITAL - ‘Ainun Najib, Muhammad Fikri; Rohman, Miftakhul (Universitas Nahdlatul Ulama Blitar, 2024)
The development of digital technology has brought a significant transformation in human communication patterns, including political communication and da'wah education. This research explores the correlation between the use of new media in political communication and da'wah education in the digital era. Using a qualitative content analysis approach, this research examines related literature as well as case studies of the use of digital platforms by political figures and preachers. The research results show that new media facilitates the delivery of messages interactively, quickly and widely, both for building a political image and spreading Islamic values. However, there are challenges in the form of spreading hoaxes, polarizing opinions, and content moderation. The correlation between the two includes similar strategies, such as the use of social media algorithms, creative visualization, and compelling narratives. This research concludes the importance of digital literacy and a strategic approach to maximize the potential of new media in political communication and da'wah, while maintaining the ethics and authentic value of the message.